Improving membrane photobioreactor performance by reducing light path: operating conditions and key performance indicators. (1st April 2020) - González-Camejo, J.; Aparicio, S.; Jiménez-Benítez, A.; Pachés, M.; Ruano, M.V.; Borrás, L.; Barat, R.; Seco, A.
Abstract: Microalgae cultivation has been receiving increasing interest in wastewater remediation due to their ability to assimilate nutrients present in wastewater streams. In this respect, cultivating microalgae in membrane photobioreactors (MPBRs) allows decoupling the solid retention time (SRT) from the hydraulic retention time (HRT), which enables to increase the nutrient load to the photobioreactors (PBRs) while avoiding the wash out of the microalgae biomass. The reduction of the PBR light path from 25 to 10 cm increased the nitrogen and phosphorus recovery rates, microalgae biomass productivity and photosynthetic efficiency by 150, 103, 194 and 67%, respectively.The areal biomass productivity (aBP) also increased when the light path was reduced, reflecting the better use of light in the 10-cm MPBR plant. The capital and operating operational expenditures (CAPEX and OPEX) of the 10-cm MPBR plant were also reduced by 27 and 49%, respectively. Discharge limits were met when the 10-cm MPBR plant was operated at SRTs of 3–4.5 d and HRTs of 1.25–1.5 d. At these SRT/HRT ranges, the process could be operated without a high fouling propensity with gross permeate flux (J20 ) of 15 LMH and specific gas demand (SGDp ) between 16 and 20 Nm 3 air ·m −3 permeate, which highlights the potential of membrane filtration in MPBRs. When the continuous operation of the MPBR plant was evaluated, an optical density of 680 nm (OD680) and soluble chemical oxygen demand (sCOD) were found to be good indicators of microalgae cell and algal organic matter (AOM) concentrations, while dissolved oxygen appeared to be directly related to MPBR performance. Nitrite and nitrate (NOx ) concentration and the soluble chemical oxygen demand:volatile suspended solids ratio (sCOD:VSS) were used as indicators of nitrifying bacteria activity and the stress on the culture, respectively. These parameters were inversely related to nitrogen recovery rates and biomass productivity and could thus help to prevent possible culture deterioration. Graphical abstract: Image 1 Highlights: Reducing the light path from 25 to 10 cm increased MPBR performance. Shorter light path improved the photosynthetic efficiency of microalgae. Light path reduction implied the decrease of membrane flux from 26 to 15 LMH. Legal discharge limits were successfully met. NOx and sCOD:VSS could be used to prevent possible culture deteriorations.